Arteriovenous Fistula Intervention on Snuffbox Area: A Systematic Review - Andy A. Hamisi; Yuansun Khosama; Djony E. Tjandra (Universitas Baiturrahmah, 2026)
The anatomical snuffbox arteriovenous fistula (ASB-AVF) is the most distal upper-extremity configuration for haemodialysis access and fits well with distal-first, vessel-preserving strategies, yet its clinical adoption remains limited despite endorsement as a first-line option in anatomically suitable patients. This systematic review, conducted according to PRISMA guidelines, used PubMed, the Cochrane Library, and Google Scholar to identify English-language human studies on ASB-AVF published between 1 August 2024 and 2 October 2025, using combinations of “snuffbox,” “fistula,” and “distal-radial” as search terms. Eligible studies were assessed for anatomical criteria, patency, complications, and clinical implementation, and interpreted within five conceptual frameworks: distal-first/vascular access preservation, haemodynamic optimisation, hand ischaemia and complication minimisation, patient-centred vascular access care, and access lifecycle theory. Overall, the literature indicates that ASB-AVF can achieve high early and long-term patency rates (around 84.6–>90%) while preserving proximal radial segments, reducing tissue trauma, and minimising complications such as steal syndrome and neo-intimal hyperplasia. Outcomes are strongly influenced by vessel calibre, comorbidities (especially diabetes and peripheral arterial disease), and operator expertise. Barriers to broader use include small, heterogeneous cohorts, technical complexity, dependence on ultrasound-guided access, and surgeon familiarity with conventional wrist or upper-arm AVFs. Standardised training, refined selection tools, and personalised nursing strategies represent key opportunities to optimise results and support ASB-AVF as a feasible first-line option in selected patients.